Hubungan Dukungan Suami terhadap Kesiapan Psikologis Ibu Hamil Primigravida dalam Mencapai Peran Sebagai Ibu - Nanda Adi Utami; Hernandia Distinarista; Apriliani Yulianti Wuriningsih; Sri Wahyuni (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aimed to examine the relationship between husband’s support and psychological readiness among primigravida pregnant women in achieving the maternal role. A quantitative cross-sectional design was applied involving 96 primigravida women in the first trimester who attended antenatal care at a primary health center. Data were collected using validated questionnaires measuring husband’s support and psychological readiness. Statistical analysis was performed using univariate analysis and Spearman rank correlation. The findings revealed a significant positive association between husband’s support and psychological readiness, indicating that higher levels of perceived support were related to better psychological preparedness for motherhood. Emotional, informational, and instrumental support contributed to reduced anxiety and enhanced mental readiness during early pregnancy. These results highlight the importance of partner involvement in maternal health services and emphasize that psychological readiness for motherhood is shaped not only by individual factors but also by interpersonal dynamics within the family. Integrating husband-focused interventions into antenatal care may improve maternal psychological outcomes and support a healthier transition to the maternal role.